Patient safety culture in health care facilities in Ukraine (message 1) - A.P. Yavorovsky; M.M. Rygan; A.N Naumenko; Yu.N. Skaletsky; S.G. Gichka; A.V. Ivanko; R.P. Brukhno; A.K. Gorval (Medičnì Perspektivi, 2021)
Using a questionnaire from the United States Agency for Research and Quality in Health Care (AHRQ), the characteristics of patient safety (PS) culture in the staff of various health care facilities (HCF) in Ukraine were analyzed. In addition, the characteristics of PS culture were analyzed depending on the length of service and affiliation of the respondents to the medical or nursing staff, as well as the profile of therapeutic or surgical activities. It is established that the weakness of the PS culture of the staff of domestic HCF is "Reaction to mistakes" (less than 30% of positive responses), which indicates the predominance of culture of accusation (unfair culture) in Ukrainian HCF and as a consequence fears of the staff to disclose mistakes and accordingly, the lack of opportunity to learn from these mistakes.“Staffing” is identified as a weakness of the PS culture (less than 50% of positive responses) in most comparison groups. It is worth noting such a characteristic of the culture of BP, as the "Frequency of error messages" (less than 70% of positive responses). The Cronbach's alpha coefficient in all groups of respondents ranged from 0.62 to 0.78, which indicates the truth of the results of the study.